2005
DOI: 10.1086/426935
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive Interaction and Scaling Violation inpp →π 0Interaction and GeV Excess in Galactic Diffuse Gamma‐Ray Spectrum of EGRET

Abstract: We present here a new calculation of the gamma-ray spectrum from pp ! 0 in the Galactic ridge environment. The calculation includes the diffractive p-p interaction and incorporates the Feynman scaling violation for the first time. Galactic diffuse gamma-rays come, predominantly, from 0 ! in the sub-to multiple GeV range. Hunter et al. found, however, an excess in the GeV range (''GeV excess'') in the EGRET Galactic diffuse spectrum above the prediction based on experimental pp ! 0 cross sections and the Feynma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 67 publications
5
89
3
Order By: Relevance
“…This work is an extension of that by Kamae et al (2005), where up-to-date knowledge of the 0 yield in the p-p inelastic interaction has been used to predict the Galactic diffuse gammaray emission. The authors have found that past calculations (Stecker 1970(Stecker , 1973(Stecker , 1990Strong et al 1978;Stephens & Badhwar 1981;Dermer 1986aDermer , 1986bDermer , 2000Mori 1997) had left out the diffractive interaction and the Feynman scaling violation in the nondiffractive inelastic interaction.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…This work is an extension of that by Kamae et al (2005), where up-to-date knowledge of the 0 yield in the p-p inelastic interaction has been used to predict the Galactic diffuse gammaray emission. The authors have found that past calculations (Stecker 1970(Stecker , 1973(Stecker , 1990Strong et al 1978;Stephens & Badhwar 1981;Dermer 1986aDermer , 1986bDermer , 2000Mori 1997) had left out the diffractive interaction and the Feynman scaling violation in the nondiffractive inelastic interaction.…”
Section: Introductionmentioning
confidence: 98%
“…The formulae are derived from the up-to-date p-p interaction model by Kamae et al (2005), which incorporates the logarithmically rising inelastic cross section, the diffraction dissociation process, and the Feynman scaling violation. To improve fidelity to experimental data in lower energies, two baryon resonance contributions have been added: one representing Á(1232) and the other representing multiple resonances around 1600 MeV/c À2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[97] and the inclusion of diffractive interactions and scaling violations in Ref. [98] (see the Appendix of Ref. [99] for a a comparison of different approaches).…”
Section: Photo-disintegration Vs π Decaymentioning
confidence: 99%